Left sided Richter type obturator hernia causing intestinal obstruction: A case report. (December 2018) - Ayoub, Kusay; Mahli, Nihad; Dabbagh, M. Fateh; Banjah, Bashar; Banjah, Bassel
Abstract: Introduction: Although relatively rare, an obturator hernia is a significant cause of intestinal obstruction. It usually occurs in emaciated elderly females. Computed tomography is the imaging modality of choice to diagnose obturator hernias. Case report: In this report we present a case of an elderly female who presented to the emergency department with features suggesting bowel obstruction. The patient was admitted to the hospital and was initially managed conservatively. Two days later the patient underwent an exploratory laparotomy and was diagnosed with a left sided Richter type obturator hernia. The hernia was successfully reduced and the necrotic bowel was resected with end to end anastomosis. Discussion: An obturator hernia is a rare type of abdominal hernias which often occurs in very thin old females. Patients with obturator hernias usually present with symptoms of acute or intermittent small bowel obstruction. Mild symptoms without abdominal pain may be due to incomplete obstruction or Richter type hernia. Computed tomography is considered the gold standard diagnostic modality for obturator hernias. An early surgical intervention is the treatment of choice. Conclusion: The clinical diagnosis of an obturator hernia is often difficult due to its nonspecific symptoms and infrequent signs. Yet early diagnosis is mandatory because its delay contributes to bowel necrosis and to the poor prognosis in these patients. Surgery remains the only effective management of this condition. Highlights: Obturator hernias are a rare cause of intestinal obstruction. An obturator hernia usually occurs in very thin elderly females. Obturator hernias present with symptoms of intestinal obstruction. Computed tomography is the imaging modality of choice to diagnose obturator hernias. The only management of this condition is surgery through either laparotomy or laparoscopy.